A new species of Ahaetulla Link, 1807 (Squamata: Colubridae) from the Mekong Delta, Vietnam - Lam, Ngon Quang; Thu, Tran Thi Anh; Nguyen, Luan Thanh; Murphy, Robert W.; Nguyen, Sang Ngoc (Zootaxa, 2021)
A new vine snake, genus Ahaetulla, from Soc Trang Province, southern Vietnam is described based on morphological data and nucleotide sequences from COI and Cytb. Ahaetulla rufusoculara sp. nov. is diagnosed by the following morphological characters: bright red eyes; snout without dermal appendage; internasal separated from supralabial by loreal; body scale rows 15-15-13; ventrals 186–190 in males and 182–185 in females; subcaudals 143–153 in males and 128 or 129 in females; 8 (rarely 9) supralabials, fourth and fifth or fourth to sixth entering orbit; 12–14 maxillary teeth; hemipenis short, reaching 6th or 7th SC; cloacal plate divided; dorsum bright green; and yellow or white stripe along the lower flank. The new species differs from its congeners by an uncorrected p-distance in COI and Cytb sequences of at least 7.7% and 7.5%, respectively.